Interleukin-1 receptor-associated kinase-M suppresses systemic lupus erythematosus. Issue 12 (29th August 2011) - Lech, Maciej; Kantner, Claudia; Kulkarni, Onkar P; Ryu, Mi; Vlasova, Ekaterina; Heesemann, Jürgen; Anz, David; Endres, Stefan; Kobayashi, Koichi S; Flavell, Richard A; Martin, Javier; Anders, Hans-Joachim
Abstract : Objectives: Interleukin-1 receptor-associated kinase (IRAK)-M suppresses Toll-like receptor (TLR)-mediated activation of innate immunity during infection. A similar role was hypothesised for IRAK-M in autoimmunity. Methods: Irak-m-deficient mice were crossed with autoimmune C57BL/6-lpr/lpr mice and detailed phenotype analysis was performed. Results: Irak-m deficiency converted the mild autoimmune phenotype of C57BL/6-lpr/lpr mice into a massive lymphoproliferative syndrome with lethal autoimmune lung disease and lupus nephritis. Irak-m deficiency induced a number of interferon-related genes, cytokines and plasma cell survival factors in spleen cells of these mice. Irak-m-deficient C57BL/6-lpr/lpr mice showed expansion of autoreactive T cells, dysfunctional regulatory T cells and plasma cells which was associated with increased lupus autoantibody production. TLR7 antagonism almost completely abrogated this phenotype consistent with IRAK-M-mediated suppression of TLR7 signalling in vitro. Conclusions: These data identify a previously unknown function of IRAK-M—namely, suppression of TLR7-mediated autoimmunity—and mutant IRAK-M as a previously unknown genetic risk for murine SLE.